Utilization of Durian Peel as Adsorbent in Tofu Industrial Wastewater Treatment - Dennis Farina Nury; Misbahul Huda; Hendri Kurniawan; Tulusma Basana Simaremare; Abdul Halim; Alfira Putri Damayanti; Didik Supriyadi; Deviany Deviany; Feerzet Achmad; Muhammad Zulfikar Luthfi; Andri Saputra (Politeknik ATK Yogyakarta, 2025)
Tofu industry wastewater in Indonesia contains high concentrations of organic pollutants, especially chemical oxygen demand (COD), which often exceed regulatory discharge limits due to the lack of effective treatment systems in small-scale production units. This study was conducted to evaluate the performance of durian peel as a low-cost adsorbent for COD removal. The adsorbent was prepared through carbonization at 300°C for 1 hour and activated using 30% H₃PO₄ for 24 hours. Batch adsorption experiments were conducted by varying contact time (0–150 minutes) and adsorbent dosage (0.2–1.0 g) at constant shaking speed (150 rpm). The result showed that activated durian peel demonstrated potential as an adsorbent for tofu wastewater, though its iodine number fell below the SNI 06-3730-1995 standard. The optimum condition was achieved at 90 minutes and 0.6 g adsorbent, resulting in 85.75% COD removal. Adsorption equilibrium data were analysis using Langmuir and Freundlich isotherm models. The Freundlich model provided a better fit (R² = 0.7663), indicating multilayer adsorption on a heterogeneous surface. These findings confirm the potential of durian peel as an effective biosorbent for tofu wastewater treatment under optimal adsorption conditions.